ANALISIS PERAN KEPEMIMPINAN DALAM PENGELOLAAN BUDAYA ORGANISASI DI KANTOR KECAMATAN SIROMBU KABUPATEN NIAS BARAT - Ivan Julius Hia; Palindungan Lahagu; Robin Markus Putra Waruwu; Serniati Zebua (Jurnal Publikasi Manajemen Informatika, 2026)
This study aims to analyze the role of leadership in managing organizational culture at the Sirombu District Office, West Nias Regency. The research employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The informants consisted of the Head of Sirombu District, structural officials, employees, and community members who were selected based on their involvement and understanding of the research object. The findings indicate that leadership plays a crucial role in developing organizational culture through open communication, exemplary behavior, motivation, guidance, and employee supervision. Effective leadership contributes to improving discipline, responsibility, teamwork, professionalism, and the quality of public services. However, the management of organizational culture still faces several challenges, including differences in employees’ mindsets, resistance to change, low discipline among some employees, limited facilities and infrastructure, and uneven employee participation in supporting organizational programs. To address these challenges, leaders have implemented various strategies, such as regular communication, personal coaching, persuasive and family-oriented approaches, performance evaluation, training programs, and employee motivation. The study also reveals that a positive organizational culture has a significant impact on improving public service quality, employee responsiveness, and community satisfaction. Therefore, strengthening organizational culture should be carried out continuously through enhanced communication, employee competency development, periodic evaluation, and the active involvement of all organizational members in achieving organizational goals.